2016
DOI: 10.1088/1367-2630/18/9/095002
|View full text |Cite
|
Sign up to set email alerts
|

Laser assisted tunneling in a Tonks–Girardeau gas

Abstract: We investigate the applicability of laser assisted tunneling in a strongly interacting one-dimensional (1D) Bose gas (the Tonks-Girardeau gas) in optical lattices. We find that the stroboscopic dynamics of the Tonks-Girardeau gas in a continuous Wannier-Stark-ladder potential, supplemented with laser assisted tunneling, effectively realizes the ground state of 1D hard-core bosons in a discrete lattice with nontrivial hopping phases. We compare observables that are affected by the interactions, such as the mome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
(158 reference statements)
0
1
0
Order By: Relevance
“…In particular, it is shown that an initial Bose-Einstein condensate in a periodically driven optical lattice may become unstable due to two-body collisions [29] or through the mechanism of parametric resonance [28,[30][31][32][33][34][35][36]. The preparation protocol, stability and a lifetime of strongly correlated phases, expected in the regime of strong interactions under driving is a highly debated topic at the moment [28,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is shown that an initial Bose-Einstein condensate in a periodically driven optical lattice may become unstable due to two-body collisions [29] or through the mechanism of parametric resonance [28,[30][31][32][33][34][35][36]. The preparation protocol, stability and a lifetime of strongly correlated phases, expected in the regime of strong interactions under driving is a highly debated topic at the moment [28,37,38].…”
Section: Introductionmentioning
confidence: 99%